Pay-as-you-go OWL query answering using a triple store - Zhou, Y; Nenov, Y; Grau, BC; Horrocks, I (AAAI Press, 2014)
We present an enhanced hybrid approach to OWL query answering that combines an RDF triple-store with an OWL reasoner in order to provide scalable pay-as-you-go performance. The enhancements presented here include an extension to deal with arbitrary OWL ontologies, and optimisations that significantly improve scalability. We have implemented these techniques in a prototype system, a preliminary evaluation of which has produced very encouraging results.